The Least Eigenvalue of the Complement of the Square Power Graph of G. (16th September 2021) - Gul, Lubna; Ali, Gohar; Waheed, Usama; Nasir, Sumiya
Abstract : Let G n, m represent the family of square power graphs of order n and size m, obtained from the family of graphs F n, k of order n and size k, with m ≥ k . In this paper, we discussed the least eigenvalue of graph G in the family G n, m c . All graphs considered here are undirected, simple, connected, and not a complete K n for positive integer n .